Mapping the terrain of social media misinformation: A scientometric exploration of global research - Jian Wang; Yujia Zhai; Fakhar Shahzad (Acta Psychologica)
The rise of social media has enabled unrestricted information sharing, regardless of its accuracy. Unfortunately, this has also resulted in the widespread dissemination of misinformation. This study aims to provide a comprehensive scientometric analysis under the PRISMA paradigm to clarify the repetitive trajectory of misinformation on social media in the current digital age. In this study, 3724 publications on social media misinformation from the Web of Science between January 2010 and February 2024 were analyzed scientifically and metrically using CiteSpace software. The findings reveal a sharp increase in annual publication output starting from 2015. The United States of America and China have made more significant contributions in publication volume and global collaborations than other nations. The top five keywords with high frequency are social media, fake news, information, misinformation, and news. In contrast to a brief review of existing articles, this study provides an exhaustive review of annual scientific research output, journals, countries, institutions, contributors, highly cited papers, and keywords in social media misinformation research. The developmental stages of social media misinformation research are charted, current hot topics are discussed, and avenues for future research are suggested.